Effectiveness of New Systemic Insecticides on Rice Leaffolder (Cnaphalocrocis Medinalis Guenée) and Influence on Beneficial Insect Fauna (Journal of Agriculture and Biology, 2025)
The rice leaffolder (Cnaphalocrocis medinalis Guenée) is a prominent pest of rice crops, resulting in substantial yield reductions globally. This study aimed to examine the effectiveness of novel systemic insecticides against C. medinalis while examining their effects on beneficial insect populations, essential for formulating sustainable pest management methods in rice agriculture. Fourteen systemic insecticides were assessed for their effectiveness against C. medinalis and their effects on beneficial insect populations. Insecticides were administered at prescribed field rates utilizing calibrated apparatus, with monitoring performed pre-treatment and at 72 hours and one-week post-treatment to evaluate pest death and the survival of beneficial insects. The pre-treatment populations of C. medinalis varied from 9.80 to 11.87 larvae per square metre, while the control group had an average of 10.87 larvae per square meter. Monitoring after treatment at 72 hours and one week indicated substantial decreases in insect numbers. Milzon 0.30% G, forecast 0.69% G, and Sirma 0.45% G shown the highest efficacy, with mortality rates of 90.72%, 88.82%, and 89.67% at 72 hours, and 95.71%, 92.88%, and 93.94% after one week, respectively. Conversely, Rector Super 0.35% G and the control group had no efficacy, with mortality rates of 79.26% and 0.00%, respectively. The survival rates of beneficial insects were highest in the control group (148.42%), followed by Forecast 0.69% G (72.06%), Milzon 0.30% G (71.66%), and Sirma 0.45% G (69.53%). The lowest survival rates were recorded for Power Drop 5.12% G (67.59%) and Agral Plus 5.44% G (65.90%). The results underscore the necessity of choosing insecticides that efficiently manage C. medinalis while reducing adverse effects on beneficial insects. It has been shown that Milzon 0.30% G, forecast 0.69% G, and Sirma 0.45% G are viable solutions for integrated pest control in rice agriculture. These alternative methods efficiently bring ecological sustainability and pest control into harmony with one another. It is recommended to conduct further research for the determination of long-term impact of these insecticides as well as to incorporate these insecticides with other pest control methods.